IMPLEMENTATION OF MERDEKA MANDIRI CURRICULUM CHANGES IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT UPT SMP NEGERI 2 GRESIK - Fia Ayu Putri Agustin; Amrullah Amrullah; Abd. Muqit; Usman Yudi (LP2M Universitas Ibrahimy, 2024)
The Merdeka Mandiri curriculum is the curriculum chosen by UPT SMP Negeri 2 Gresik to implement the independent curriculum initiated by the Minister of Education and Culture, Nadiem Makarim. This research aims to determine the design of the Merdeka Mandiri curriculum that has changed Islamic Religious Education learning and the implementation of the Merdeka Mandiri curriculum that has changed the learning of Islamic Religious Education, as well as evaluate the Merdeka Mandiri curriculum that has changed in the learning of Islamic Religious Education. To achieve the objectives of this research, qualitative research was the choice to reveal the implementation of the independent learning curriculum, especially in Islamic Religious Education learning with the method used to collect data: interviews, observations, and documentation. Meanwhile, the data analysis techniques used are data condensation, data presentation, and concluding. The results of the research are the design of the Merdeka Mandiri Curriculum Changes in Islamic Religious Education learning in accordance with the central learning outcomes and developed by teachers in charge of Islamic Religious Education through teaching modules, the implementation of the Merdeka Mandiri Changed Curriculum in Islamic Religious Education learning is carried out in accordance with the teacher's understanding and when there are problems in the process solutions were sought for learning together through MGMPS Islamic Religious Education and teacher meetings. Evaluation of the Merdeka Mandiri Changed Curriculum for Islamic Religious Education learning was carried out internally from UPT SMP Negeri 2 Gresik and externally from the Education supervisor at the end of the semester.